The effects of adding a six-month Pilates exercise program to three months of traditional community-based pulmonary rehabilitation in individuals with COPD: A prospective cohort study - Marisela Barbosa; Cristina A. de Melo; Rui Torres (Canadian Journal of Respiratory Therapy)
# Introduction